Comparison between DOACs and warfarin for left atrial thrombus in atrial fibrillation patients - Akihiro Sunaga; Daisaku Nakatani; Katsuki Okada; Hirota Kida; Yuki Matsuoka; Daisuke Sakamoto; Tetsuhisa Kitamura; Nobuaki Tanaka; Yasuyuki Egami; Masaharu Masuda; Tetsuya Watanabe; Hitoshi Minamiguchi; et al. (International Journal of Cardiology: Heart & Vasculature)
Background: Atrial fibrillation (AF) is a major risk factor for thromboembolic events, with left atrial thrombus (LAT) formation occurring despite oral anticoagulant (OAC) therapy in some patients. Direct oral anticoagulants (DOACs) have demonstrated efficacy in preventing thrombosis; however, their role in LAT resolution compared to warfarin remains unclear. Methods: This retrospective, multicenter study analyzed 260 AF patients with transesophageal echocardiography (TEE)-confirmed LAT among 17,436 AF patients who underwent TEE. Patients were categorized into DOAC and warfarin groups. LAT resolution, ischemic stroke/systemic embolism, major bleeding, and all-cause death were evaluated. The warfarin group was further stratified by time in therapeutic range (TTR) (<60 % and ≥ 60 %), and the DOAC group by dose (standard and low). Results: During a median follow-up of 386 [367, 413] days, LAT resolution was achieved in 62 % of patients, significantly higher in the DOAC group (74 % vs. 54 %, P = 0.001). Standard-dose DOACs had the highest resolution rates, while TTR < 60 % had the lowest (79 % vs. 49 %). DOACs were independently associated with higher LAT resolution (OR = 2.91 [1.32–6.38], P = 0.008) and fewer bleeding events (OR = 0.26 [0.08–0.80], P = 0.019). Conclusions: DOAC therapy was associated with higher LAT resolution rates and showed a fewer bleeding events compared to warfarin. DOACs may serve as first-line therapy for LAT.